The Location of the Tatar Shlyakh Trade Road from Azaq to Lviv along the Northern Coast of Sea of Azov and Black Sea (according to numismatic data) - Khromov K.K. (Золотоордынское обозрение)
Research objectives: The presentation of an inferred location of the Tatar Shlyakh trade road from Azaq to Lviv along the northern coast of the Sea of Azov and Black Sea. The external and internal factors and political processes in the ulus of Jochi and their influence on the direction and period of operation of the road and its development. The period of operation of this road is defined according to numismatic data. Research materials: “Pratica della mercatura” by Francesco Pegolotti, “Kodeks dyplomatyczny miasta Krakowa 1257–1506”, “Diplomatarium veneto-levantinum sive Acta et diplomata res venetas …”, medieval maps, a physical map and map of the rivers of Ukraine, a topographical study of coin finds on the territory of modern Nikolaev and Kherson regions of Ukraine. Results and novelty of the research: The exact route of the Tatar Shlyakh trade road from Azaq to Lviv along the northern coast of the Azov and the Black Seas is currently not exactly known. Modern researchers make a lot of mistakes, while trying to reconstruct it. They do not take into account the geographical features of the territory, political processes, and economic processes in the western part of the ulus of Jochi. Likewise, military clashes in the Crimea and in the western part of the ulus of Jochi at the beginning of the fourteenth century have been ignored. Some modern researchers believe that the route began in the city of Caffa on the Black Sea. Nevertheless, we took this data into account and recognized the part of the route from Caffa through Solkhat and Perekop as a branch of the main route. The topography of the finds of Jochid coins on the alleged stretch of the road was examined and used in this study. This topography indicates the possible location of another crossing over the Dnieper in the area of Adzhigolskaya Balka on the right bank of the Dnieper estuary. Two periods of the existence of this road in 1280–1300 and 1350–1390 are established according to numismatic data.